2002
DOI: 10.1002/humu.9056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thePTCH coding region in human rhabdomyosarcoma

Abstract: Inherited mutations of the human tumor suppressor gene Patched (PTCH) lead to an autosomal dominant disorder known as Nevoid Basal Cell Carcinoma Syndrome (NBCCS).The syndrome is characterized by a combination of developmental abnormalities and a predisposition to tumor formation. Tumors in patients with NBCCS include basal cell carcinoma, medulloblastoma, fibroma and rhabdomyosarcoma (RMS). RMS are also present in 15 % of mice haplodeficient for Ptch. To investigate whether mutations in PTCH are a general fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
(25 reference statements)
0
17
1
Order By: Relevance
“…Several studies identified loss of heterozygosity (8-35% of patients) and deletions (33% of patients) in band 9q22, a large region containing PTCH1 and many other genes (Tostar et al, 2005). PTCH1-specific mutations have not been detected in spontaneous RMS tumors (14 sequenced samples) (Calzada-Wack et al, 2002). This finding is surprising given findings in other Hedgehog-associated cancers; 30-40% of basal cell carcinomas and $20% of medulloblastomas Johnson et al, 1996;Wolter et al, 1997;Xie et al, 1997;Lam et al, 1999;Eberhart, 2003) have inactivating mutations in PTCH1.…”
Section: Ink4bmentioning
confidence: 95%
“…Several studies identified loss of heterozygosity (8-35% of patients) and deletions (33% of patients) in band 9q22, a large region containing PTCH1 and many other genes (Tostar et al, 2005). PTCH1-specific mutations have not been detected in spontaneous RMS tumors (14 sequenced samples) (Calzada-Wack et al, 2002). This finding is surprising given findings in other Hedgehog-associated cancers; 30-40% of basal cell carcinomas and $20% of medulloblastomas Johnson et al, 1996;Wolter et al, 1997;Xie et al, 1997;Lam et al, 1999;Eberhart, 2003) have inactivating mutations in PTCH1.…”
Section: Ink4bmentioning
confidence: 95%
“…44,45 Chromosomal translocations in ARMS lead to the expression of PAX3/FKHR or PAX7/FKHR fusion proteins that correlate with poorer treatment outcomes. 46 Other oncogenes and cell cycle modulators, including TP53 and MDM2, [47][48][49][50][51] cyclin-dependent kinase inhibitor (CDKN)2A, [52][53][54][55] AKT, 56,57 phosphatase and tensin homolog (PTEN), 58,59 survivin, 60,61 RAS, 62 PTCH, [63][64][65] …”
mentioning
confidence: 99%
“…Controversially, Calzada et al, did not detect mutations in the coding sequence of PTCH1 in 14 RMS sequenced [47]. This is corroborated by another study showing absence of PTCH1 loss-of-function mutations or SMO amplifications in 26 NRMS examined [41].…”
Section: Role Of Hedgehog Pathway In Rmsmentioning
confidence: 88%